Czy piękni dwudziestoletni? Plany i wartości życiowe maturzystów z Dąbrowy Górniczej i Tychów = Will Beautiful Twenty-Year-Olds? Plans and Life Values of Secondary-School Graduates from Dąbrowa Gornicza and Tychy - Matusik, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to present the research results concerning, among the others, chosen identity elements, plans for life and value systems of secondary school students (general and technical secondary schools) in Dąbrowa Gornicza and Tychy. It seemed interesting to learn the way young people, born in 1989 (the year when, according to Joanna Szczepkowska`s words "Communism ended in Poland") view the world around them. The sociological survey covered over 2000 graduates from Tychy and Dąbrowa Gornicza, who took their Matura Examination in the spring of 2009.
Keywords: szkolnictwo ponadpodstawowe; plany życiowe; Dąbrowa Górnicza; Tychy